2011
DOI: 10.1111/j.1365-263x.2011.01146.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries prevalence and its association with brushing habits, water availability, and the intake of sugared beverages

Abstract: BACKGROUND. With Dental Caries being the most common disease amongst children in the world today, there is a need to fully understand risk factors that may be related to caries prevalence and how they could be best addressed. AIM. The aim of this study was to evaluate soda, juice, sugared-beverage intake, brushing habits, and community water source availability as they relate to the prevalence of both noncavitated and cavitated caries lesions in small rural villages in Mexico. DESIGN. The International Caries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 20 publications
2
30
4
2
Order By: Relevance
“…This augments the notion that low frequency and improper tooth brushing methods are closely associated with early TD. [14] Parents’ characteristics, particularly schooling level and positive attitude towards oral health and dental care were found to be associated with more favorable pattern of tooth brushing in children. [15] Thus, parents need to brush the teeth of the children daily, using fluoridated children toothpaste starting the day of the appearance of the first milk tooth.…”
Section: Discussionmentioning
confidence: 99%
“…This augments the notion that low frequency and improper tooth brushing methods are closely associated with early TD. [14] Parents’ characteristics, particularly schooling level and positive attitude towards oral health and dental care were found to be associated with more favorable pattern of tooth brushing in children. [15] Thus, parents need to brush the teeth of the children daily, using fluoridated children toothpaste starting the day of the appearance of the first milk tooth.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that individuals with higher SOC scores had higher intake of fruits but lower intakes of energy, total and saturated fat, sucrose, and sweets, which indicates that individuals with a higher SOC score were better in “healthy” food choices [13]. Excessive intake of sugar products not only increases the risk of early childhood caries [24], it also increases the risk of childhood obesity [25]. Thus, the present study could provide new, useful information regarding the promotion of oral health and general health among Chinese children who are looked after by grandparents.…”
Section: Discussionmentioning
confidence: 99%
“…The increased availability of more decaying-inducing snacks and beverages appears to hold a dynamic trade-off with the strong decrease simultaneously seen when community water supplies were available in a given community: the inverse proportions of liquid intake made up by high-calorie, cariogenic beverages and by potable water have been highlighted for Mexico at large 35 . Although the rate of consumption of soft drinks in rural areas of the State of Hidalgo is somewhat lower than in urban settings and the more affluent Mexico City and Northern border regions 36 , its population nevertheless contributes to the fact that Mexico is second in the world soft drink consumption ranking 37 , and studies shows that the majority of children in the municipality of Calnali consume sugared beverages 38,39 . However, whether better roads are in fact associated with easier access to cariogenic foods and beverages remains uncertain.…”
Section: Discussionmentioning
confidence: 99%